Using computers in the law office - Cornick, Matthew S. (Cengage Learning, 2019)
"Equip yourself for career success with this bestselling guide, which explores how computers can make paralegals and legal professionals more productive on the job. USING COMPUTERS IN THE LAW OFFICE, Eighth Edition, provides comprehensive coverage of computer concepts, including the latest versions of common programs like Microsoft Word, Excel, and PowerPoint, and specialized applications such as CaseMap, Clio, HotDocs, TimeMap, and TrialDirector. With a clear and engaging writing style, real-life examples, helpful tutorials, ethical considerations, and detailed hands-on exercises to help you apply what you learn to realistic professional tasks, this proven resource will help you develop the knowledge and skills you need to succeed in today's legal organizations."--